Women’s Language Features Used By Female Characters In Cruella Movie - I Nyoman Tri Ediwan; Ni Komang Trisna Kiranidewi; I Made Netra (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aimed to identify the features of women's language used by the female characters of the Cruella movie. The types of women's language features were identified based on the theory proposed by Coates (2013). The data of this study were taken from the female characters’ speech in the movie through observation and documentation methods. Screenshot and note-taking techniques were also used in the process of collecting the data in order to maintain the detail and accuracy of the data. The collected data were classified into the category of women's language features and analysed descriptively using qualitative research methods. The research findings were presented in the form of conversation from the data chosen that presented above the analyzing description. The results of this study showed that the female characters used all types of women's language in the movie Cruella, including; minimal responses, questions, hedges, tag questions, swearing and taboo language, compliments, and commands and directives.